(3TQM bUjOI Pi GdQeIs - (3ZjdGf Hf YbHI Hf fgjS Hf eSYhO GdYOhj, ef eVQ, CHh GdMGQK, Ph GdQeI,J (B117 (3g` s ((3Ydi GdHgGQ s)
(3ChdgG (B:s
(3eG HGd Yjfjc efgG GdeGA jfScH cCfg ef cdi eaQjI SQH eG HGd Yjfjc Gi eGMGdgG s
(3BNQgG (B:s
(3cGf GYfGbgG cQGK SGFZI WGQJ daGjag Ch gjTQ SdHJ bO RGdJ Yfg bThQg JeJ GdbUjOI s
(3cJHgG Ydi GdHgGQ cGf JPcQI deNOheg HgGA GdedI hGdOjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B44s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs